Notes Towards a Multifaceted Approach to Political Stability - Radu Carp; Łukasz Perlikowski (Polish Political Science Yearbook, 2024)
This paper seeks to improve comprehension of issues related to political stability. The primary elucidating tool employed is the multifaceted approach to political stability. This is the idea that similar political stability mechanisms can be observed in many different political contexts. These phenomena consist of conspicuous discrepancies between the stability of dimensions or layers of the political sphere. The lack of congruency between political stability and economic stability, differences between the stability of government authorities and the stability of the whole political system, or the gap between social and political stability are examples that are not difficult to grasp in ordinary observations of political appearances. The main task of this paper is to explain and elaborate on the reasons behind this phenomenon. As an additional value, some suggestions of how our findings can change the view on the method of research on political stability are to be found. The outcome of our investigation can be applied to comparative politics, constitutional studies, and political system analysis. The paper is particularly significant for empirically oriented political theory.